2001
DOI: 10.1007/s10201-001-8030-8
|View full text |Cite
|
Sign up to set email alerts
|

Environmental chemistry of rivers and lakes, Part VII. Fractionation by calculation of suspended particulate matter in Lake Biwa into three types of particles of different origins

Abstract: During the period from July 1992 to March 1995, suspended particulate matter in Lake Biwa was collected at 1-month intervals, and the contents of Al, Si, and P were determined. Based on the analytical data, the particulate matter was fractionated by calculation into three types of particles of different origins: particles of terrigenous origin, particles of diatom origin, and particles due to microorganisms except for diatoms. The relative abundance of the respective particles was featured in water depth-time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In contrast, freshwater diatoms usually need more Si than marine diatoms. Nagai et al (2001) reported that the Si/N and Si/P atomic ratios of diatoms collected in Lake Biwa in Japan were 3-14 times higher than the Redfield ratio. These ratios could be used for analyzing the limiting nutrients for diatoms.…”
Section: Discussion Nutrient Limitation For Diatomsmentioning
confidence: 99%
“…In contrast, freshwater diatoms usually need more Si than marine diatoms. Nagai et al (2001) reported that the Si/N and Si/P atomic ratios of diatoms collected in Lake Biwa in Japan were 3-14 times higher than the Redfield ratio. These ratios could be used for analyzing the limiting nutrients for diatoms.…”
Section: Discussion Nutrient Limitation For Diatomsmentioning
confidence: 99%
“…The high NPSS values in Lake Biwa were probably caused by terrigenous particles brought into the lake by river water following the melting of snow in spring, rainfall in early summer, and typhoons in autumn (Nagai et al 2001). In addition, NPSS values were also enhanced by the re-suspension of sediments in winter due to internal waves caused by winds (Murase et al 2005).…”
Section: Contributions Of the Oass To The Sdmentioning
confidence: 99%
“…In more recent works, suspended inorganic particles have been increasingly suspected to be the most influential substances on light penetration in many productive inland waters (Davies-Colley et al 1993;Effler and Perkins 1996;Jassby et al 1999). Suspended inorganic particles can be autochthonous (e.g., chemical precipitation; Weidemann et al 1985) or allochthonous (e.g., terrigenous; Nagai et al 2001) in origin. Suspended inorganic particles can be autochthonous (e.g., chemical precipitation; Weidemann et al 1985) or allochthonous (e.g., terrigenous; Nagai et al 2001) in origin.…”
Section: Introductionmentioning
confidence: 99%